Predictors and outcome of customer satisfaction: Moderating effect of social trust and corporate social responsibility - Sara Javed; Md. Salamun Rashidin; Jian Wang (Future Business Journal, 2021)
The study is to present an integrative model of predictors and outcome of customer satisfaction in the fast food sector of Pakistan and also examine its effects. Moreover, we also examined the contingent effect of social trust and corporate social responsibility (CSR) on the relationship between customer satisfaction and brand loyalty. Offline and online survey was conducted with four hundred fast food customers; valid data were assessed and analyzed through structural equation modeling and moderation step-by-step approach. Results demonstrate that restaurant stimuli such as food quality, service quality, atmosphere, price, restaurant location and a variety of food have strong significant effects on customer satisfaction, and customer satisfaction engendered brand loyalty. Social trust has a positive significant impact on the relationship between customer satisfaction and brand loyalty, whereas on the other side CSR has insignificant impact on the association. The study has practical implications for both restaurateurs and government. Restaurateurs should ensure the safety standards of foods, and the government can take an initiative to set proper policy and maintain the food safety standards by regulation.
Keywords: 650; Brand loyalty; Corporate social responsibility; Customer satisfaction; Fast food industry; Service quality; Social trust